Social exclusion and mental health of youths affected by parental HIV/AIDS in China: Based on a serial mediating model - Jiaojiao Wan; Lili Ji; ZheQian Wang; Junfeng Zhao; Xiaoming Li (PLoS ONE, 2025)
The mental health of youth living with patients with HIV needs focused attention. The primary source of psychological distress they experience may stem from social exclusion. Therefore, the current study was designed to explore the relationship between social exclusion and mental health among youths affected by parental HIV/AIDS in rural China. Methods 297 youths affected by parental HIV/AIDS were recruited to completed questionnaires of social exclusion, perceived stress, future orientation and mental health. The bootstrap method was used to examine the mediation effects. Results It showed that: (1) the social exclusion (M = 32.48, SD = 15.25) significantly and negatively predicted the mental health (M = 93.27, SD = 19.08). (2) Perceived stress (M = 39.28, SD = 6.35) mediated the negative effect of the social exclusion and mental health. (3) Future orientation (M = 57.44, SD = 8.15) mediated the relationship between social exclusion and mental health. (4) Perceived stress and future orientation could play a chain-mediating role in the mechanism of social exclusion affecting the mental health. Conclusions Results of this study support the Stress and Coping Theory (SCT) and demonstrate the damaging effect of perceived stress and the protective effect of future orientation in mediating the relationship between social exclusion and mental health among youths affected by parental HIV/AIDS in China. Future mental health promotion and intervention efforts targeting these youths or other youths with early childhood adversity should include components that could mitigate the negative impact of social exclusion on their lives.